2004
DOI: 10.2337/diacare.27.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Low Synthesis and High Absorption of Cholesterol Characterize Type 1 Diabetes

Abstract: OBJECTIVE -Streptozotocin-induced type 1 diabetes in experimental animals inhibits cholesterol synthesis and increases cholesterol absorption. In contrast to human type 2 diabetes, virtually no information is available on cholesterol synthesis and absorption in type 1 diabetes.RESEARCH DESIGN AND METHODS -We studied the variables of cholesterol metabolism in 27 patients with type 1 diabetes and in 10 patients with type 2 diabetes matched for body weight, using cholesterol precursor sterol ratios to cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 33 publications
3
41
1
2
Order By: Relevance
“…In two previous studies (2,3), plant sterol and cholestanol ratios were markedly increased in sera of adult type 1 diabetic subjects compared with control or type 2 diabetic subjects. In addition, cholesterol synthesis markers appeared to be low, most likely indicating reduced overall synthesis of cholesterol (2,3).…”
Section: Triads By Cholestanol Ratiosmentioning
confidence: 71%
See 1 more Smart Citation
“…In two previous studies (2,3), plant sterol and cholestanol ratios were markedly increased in sera of adult type 1 diabetic subjects compared with control or type 2 diabetic subjects. In addition, cholesterol synthesis markers appeared to be low, most likely indicating reduced overall synthesis of cholesterol (2,3).…”
Section: Triads By Cholestanol Ratiosmentioning
confidence: 71%
“…Recent studies (2,3) have suggested that in adults with type 1 diabetes, cholesterol synthesis is low and cholesterol absorption high compared with healthy individuals or subjects with type 2 diabetes. These clinical findings have been corroborated in the experimental model of streptozotocin-induced diabetes, in which expression of ABCG 5/8 genes in enterocytes and hepatocytes were reduced (4).…”
mentioning
confidence: 99%
“…cholestanol, desmosterol, and lathosterol. The results obtained in this field showed that in T1D patients the markers of cholesterol absorption were increased, while the markers of cholesterol synthesis were decreased compared with control subjects, indicating that both high cholesterol absorption and low cholesterol synthesis are present in type 1 diabetic patients [2]. This mechanism has been hypothesized to be the result of an upregulation of specific genes for the synthesis of key proteins in the process of cholesterol intestinal absorption.…”
Section: Type 1 Diabetes and Dyslipidemiamentioning
confidence: 95%
“…This fact has been established through various studies such as that of Saydah SH et al The reason that has been suggested for a lesser degree of dyslipidemia in type 1 diabetics being physiological decreased hepatic synthesis of cholesterol. 18,19 Other possible reasons for less dyslipidemia in type 1 diabetes in this study may include younger age group and more conscious lifestyle changes in patients with type 1 diabetes Some domains of cognitive functioning were spared (p>0.05) in our study that may be due to heterogeneity of the population selected, limited sample size, and a lesser degree of dyslipidemia that was observed in a study population of this area. Hence, a need of further longitudinal study for type 1 diabetics is necessary for better generalizations of results.…”
Section: Discussionmentioning
confidence: 61%